2018
DOI: 10.5888/pcd15.170577
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and Mortality in Tianjin, China: A Death Registry–Based Case-Control Study, 2010–2014

Abstract: IntroductionWe conducted a mortality case-control study to assess the risks of all-cause and major causes of death attributable to smoking in Tianjin from 2010 through 2014. The death registry–based study used data from The Tianjin All Causes of Death Surveillance System, which collects information routinely on smoking of the deceased in the death certificate of Tianjin Centers for Disease Control and Prevention.MethodsCases (n = 154,086) and controls (n = 25,476) were deaths at 35 to 79 years from smoking-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…We included all the deaths from ages 35 to 79 years during 2016–2017. The data collection and quality have been described elsewhere 10 - 12 . Briefly, the local regulation requires death certification to be completed and entered into the surveillance system by doctors of all hospitals and community health service centers in Tianjin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We included all the deaths from ages 35 to 79 years during 2016–2017. The data collection and quality have been described elsewhere 10 - 12 . Briefly, the local regulation requires death certification to be completed and entered into the surveillance system by doctors of all hospitals and community health service centers in Tianjin.…”
Section: Methodsmentioning
confidence: 99%
“…The death registration system in Tianjin is the first and only death registration system which is collecting the smoking information of the deceased in China. Starting at the end of 2009, the current research group has been collecting information routinely on smokers including: smoking status (current smoking, quit smoking, never smoked); cigarettes/day; and years of smoking recorded on the death certificate 10 , 11 . In 2015, in order to further improve the collection of data, smoking information about the duration of smoking cessation was added (if the deceased had quit, the duration of smoking abstinence in years).…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of lung cancer deaths attributable to smoking vary across populations, ranging from >80% in the United States and France to 61% in a pooled analysis of 21 Asian cohorts and 40% in sub‐Saharan Africa . Previous studies havereported that the smoking‐attributed fraction for lung cancer was 50.2% in men and 32.7% in women in Tianjin …”
Section: Discussionmentioning
confidence: 99%
“…25 Previous studies havereported that the smoking-attributed fraction for lung cancer was 50.2% in men and 32.7% in women in Tianjin. 26 In several studies, the high mortality rate in China, despite a relatively lower prevalence of female smoking compared to more developed countries, was probably due to higher exposure to secondhand smoke and indoor air pollution from unventilated combustion of coal used for heating and cooking purposes. 10,27 A meta-study showed that indoor air pollution from cooking was also a high risk to lung cancer for non-smoking Chinese women, with ORs (95% CI) as follows: kitchen smog while cooking 2.21 (1.27, 2.96), frequency of deep frying food per week 2.24 (1.61, 3.12), compared to passive smoking (at workplace in adult period 1.47 [1.28, 1.69]).…”
Section: Discussionmentioning
confidence: 99%
“…The 2009 GHK study, commissioned by the EU, summarizing the results of current economic studies, concluded that all previous studies (at least until 2009) were based on the US study CPSII (US Surgeon General) and used standardized SAF indicators from this study [7,9]. Equivalent scale study in 2010-2014 was carried out in China, where smoking annually kills a significant part of the country's economically active population [5]. Authors of economic impact calculations for smoking in different countries similarly conclude that in order to empirically and statistically verify the link between smoking and diseases in other geopolitical regions with different social, ecological, and other factors, long-term studies of similar scale should be carried out [3].…”
Section: Methodsmentioning
confidence: 99%